2013
DOI: 10.1126/science.1243417
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock NAD + Cycle Drives Mitochondrial Oxidative Metabolism in Mice

Abstract: Circadian clocks are self-sustained cellular oscillators that synchronize oxidative and reductive cycles in anticipation of the solar cycle. We found that the clock transcription feedback loop produces cycles of nicotinamide adenine dinucleotide (NAD+) biosynthesis, adenosine triphosphate production, and mitochondrial respiration through modulation of mitochondrial protein acetylation to synchronize oxidative metabolic pathways with the 24-hour fasting and feeding cycle. Circadian control of the activity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
582
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 560 publications
(626 citation statements)
references
References 43 publications
26
582
4
3
Order By: Relevance
“…Cry1/Cry2 double knock out mice exhibit arrhythmia in free running conditions. As discussed earlier however, CRY1 and CRY2 can impact on cellular metabolism with the double knockout MEFs exhibiting increased mitochondrial ATP, NAD+, FAO and decreased levels of glycolytic lactate [95]. It may be that the cryptochrome proteins promote a more glycolytic phenotype through negative regulation of the BMAL1:CLOCK heterodimer.…”
Section: The Clock Repressors: Period and Cryptochromementioning
confidence: 99%
See 3 more Smart Citations
“…Cry1/Cry2 double knock out mice exhibit arrhythmia in free running conditions. As discussed earlier however, CRY1 and CRY2 can impact on cellular metabolism with the double knockout MEFs exhibiting increased mitochondrial ATP, NAD+, FAO and decreased levels of glycolytic lactate [95]. It may be that the cryptochrome proteins promote a more glycolytic phenotype through negative regulation of the BMAL1:CLOCK heterodimer.…”
Section: The Clock Repressors: Period and Cryptochromementioning
confidence: 99%
“…4B). Mouse embryonic fibroblast (MEF) and liver cells lacking Bmal1 display a pro-glycolytic phenotype, evidenced by lower mitochondrial ATP production and higher production of lactate [95]. Levels of the oxioreductase factor nicotinamide adenine dinucleotide (NAD+) and fatty acid oxidation (FAO), which display a circadian rhythm in WT mice, were diminished in cells lacking Bmal1 leading to increased triglycerides.…”
Section: Bmal1-a Master Regulatormentioning
confidence: 99%
See 2 more Smart Citations
“…Sirt3, one subtype of the Sirt family, is located in the mitochondria, which indicates that NaB may be related to Sirt3. Previous reports have demonstrated that Sirt3 can promote the mobilization of cellular energy stores and protects cells in low‐energy states, acting as an important protector of cell viability 16. Whether Sirt3 plays an important protective role in AMI is unknown.…”
Section: Introductionmentioning
confidence: 99%